Transformation of the Role of Musyrif as Murobbi in Developing Moral Integrity and Discipline of Students at Al-Kaaffah Islamic Boarding School Kuningan - Fauzi Nurjaman; M. Jadid Khadavi (Immortalis Journal of Interdisciplinary Studies, 2026)
This study aims to analyze the transformation of the role of the musyrif as a murobbi (leader) in developing the moral integrity and discipline of students at the Al-Kaaffah Islamic Boarding School in Kuningan. The urgency of this research lies in the increasing challenges of developing student character amidst modernization, necessitating a more transformative and relevant development approach. The study used qualitative methods with a descriptive design to explore the direct experiences of musyrifs, students, and pesantren leaders. Data were obtained through participant observation, in-depth interviews, and documentation analysis. The results indicate that the transformation of the musyrif's role is realized through strengthening role models, intensive spiritual guidance, personal communication, and consistent enforcement of discipline. This role significantly influences the internalization of integrity values ​​such as honesty, responsibility, and obedience, while simultaneously enhancing discipline in learning activities and dormitory life. These findings provide a theoretical contribution to the study of pesantren character education, particularly regarding relationship-based and role-model-based development models. This study also emphasizes the importance of improving the capacity of musyrifs so that character development in pesantren can be more effective, adaptive, and sustainable.